The translational landscape of Arabidopsis mitochondria. Issue 12 (5th June 2018) - Planchard, Noelya; Bertin, Pierre; Quadrado, Martine; Dargel-Graffin, Céline; Hatin, Isabelle; Namy, Olivier; Mireau, Hakim
Abstract: Messenger RNA translation is a complex process that is still poorly understood in eukaryotic organelles like mitochondria. Growing evidence indicates though that mitochondrial translation differs from its bacterial counterpart in many key aspects. In this analysis, we have used ribosome profiling technology to generate a genome-wide snapshot view of mitochondrial translation in Arabidopsis . We show that, unlike in humans, most Arabidopsis mitochondrial ribosome footprints measure 27 and 28 bases. We also reveal that respiratory subunits encoding mRNAs show much higher ribosome association than other mitochondrial mRNAs, implying that they are translated at higher levels. Homogenous ribosome densities were generally detected within each respiratory complex except for complex V, where higher ribosome coverage corroborated with higher requirements for specific subunits. In complex I respiratory mutants, a reorganization of mitochondrial mRNAs ribosome association was detected involving increased ribosome densities for certain ribosomal protein encoding transcripts and a reduction in translation of a few complex V mRNAs. Taken together, our observations reveal that plant mitochondrial translation is a dynamic process and that translational control is important for gene expression in plant mitochondria. This study paves the way for future advances in the understanding translation in higher plant mitochondria.